CBIO-25. INTEGRATED MOLECULAR AND BH3 PROFILING OF THE INTRINSIC APOPTOTIC MACHINERY IDENTIFIES THERAPEUTIC VULNERABILITIES IN GLIOBLASTOMA. (9th November 2020) - Fernandez, Elizabeth; Mai, Wilson; Bayley, Nicholas; Tse, Christopher; Liau, Linda; Cloughesy, Timothy; Letai, Anthony; Nathanson, David
Abstract: Resistance to apoptosis is a hallmark of cancer. However, the underlying molecular mechanisms of intrinsic-apoptotic resistance in glioblastoma (GBM) are largely unknown. Here we performed integrated molecular and functional characterization (via BH3 profiling) of the intrinsic apoptotic machinery in 50 GBM patient specimens. We found that, despite significant genetic heterogeneity of our GBM samples, all GBMs have a cross compensatory reliance on BCLXL and MCL1 for basal survival. Treatment with standard of care (e.g., temozolomide or radiation) caused minimal apoptosis, yet ablated the MCL-1 block in a p53-dependent manner, thus creating an exclusive dependence on BCLXL for survival in p53 wild-type GBM tumors (65% of GBM tumors). Consequently, BCLXL inhibition caused synergistic cell death with IR/TMZ in GBM tumors with intact p53 signaling. Importantly, the degree of synergistic cell kill was best predicted by combining molecular features with BH3 profiling, providing an integrated predictive signature of response to this novel therapeutic approach. Collectively, these studies identify mechanisms of intrinsic apoptosis resistance in both basal and treatment states of GBM and demonstrate how functional and molecular data can be complementary to robustly predict therapy-induced cell death.